Juridical Analysis of Electronic Transaction Information Crime Against Gambling - Sukhebi Mofea; Beggy Tamara; Ardinal Apriliyanto (The International Journal of Law Review and State Administration, 2023)
The research objective is. To find out the legal rules regarding gambling crimes. To find out the Decision of the Tangerang District Court at No. 794/Pid.Sus/2018/PN.Tgn. For perpetrators of ITE crimes against gambling crimes. Analyze the obstacles to law enforcement and efforts to address them. The research method uses a normative legal approach qualitatively, as a system based on principles, norms, and regulations that become stipulations and court decisions. Conclusion with legal norms on criminal acts of gambling crimes in accordance with Articles 303 and 303 bis of the Criminal Code, Law no. 7 of 1974. Criminal control of gambling crimes. Proof can be analyzed by Judges from the Tangerang District Court. Decision No. 794/Pid.Sus/2018/PN.Tgn. Considering the validity of the facts and norms that were revealed in the trial, the statements obtained from witnesses and from the testimony of the accused as well as evidence became a conviction for the Judge. So that the defendant has been proven and convincingly guilty of committing a crime. Obstacles in enforcing legal norms for perpetrators of online gambling crimes through internal means. Still lacking in understanding and mastery of ITE. And lacking facilities for searching for evidence, and how to track servers accessed by online gambling managers.